INDONESIAN QUR’ANIC INTERPRETATIONS ON THE CONCEPT OF NUSHŪZ: A COMPARATIVE STUDY OF CLASSICAL AND REFORMIST APPROACHES AMONG INDONESIAN MUSLIM SCHOLARS - Pitaloka, Lolla; Manggala, Kayan; Wafi, Hasan Abdul (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2025)
The concept of nusyuz in Islamic family law, particularly as outlined in QS. An-Nisa’: 34 and 128, remains a subject of debate, especially concerning power relations within the household and the potential justification of violence against women. A conservative textual reading tends to portray women as the primary perpetrators of nusyuz, subject to escalating sanctions up to physical punishment, while nusyuz by husbands receives minimal legal attention. This imbalance is reinforced by classical interpretations shaped by patriarchal paradigms. This study addresses an academic gap by comparing the contextual-normative interpretation of M. Quraish Shihab and the feminist-progressive interpretation of Siti Musdah Mulia regarding nusyuz. Using a qualitative-descriptive approach with literature review, content and discourse analysis, hermeneutic methodology, and critical engagement with global Muslim feminist literature, this research finds that Shihab seeks to reform classical views through a contextual lens that emphasizes harmony and shared responsibility, while maintaining male leadership. In contrast, Musdah Mulia deconstructs patriarchal interpretations and emphasizes spiritual and social equality between spouses. This study contributes to the development of a fair, inclusive, and contextual discourse on gender interpretation in Indonesia and enriches the dynamics of Islam Nusantara in addressing modern challenges, particularly in family law reform and gender justice.